Cover Image. Issue 2 (6th March 2020) - Sun, Jing; Zhao, Lu; Li, Xiang; Meng, Weiyue; Chu, Dong; Yang, Xiaoyu; Peng, Peng; Zhi, Min; Qin, Siyuan; Fu, Tian; Li, Jinghao; Lu, Shaoxia; et al.
Abstract : The cover image is based on the Original Article Novel H5N6 avian infl uenza virus reassortants with European H5N8 isolated in migratory birds, China by Jing Sun et al., https://doi.org/10.1111/tbed.13380 .